(untitled) (Research, Society and Development, 2022)
The tomato has an uneven physiological maturity of the fruit, which is one of the main problems in production. To remove mucilage from the tomato seed, several methods can be used, including natural fermentation. The aim of this study was to evaluate the quality of tomato seeds under different physiological maturity stages of fruits and fermentation periods. A completely randomized design in a 2x6 factorial scheme was used. The treatments were 2 stages of fruit maturity at harvest: medium maturity and full maturity and six fermentation periods after seed extraction: 0, 2, 4, 6, 8 and 10 days. The variables analyzed were: standard germination test, field emergence, moisture content and seedling dry mass. The tomato harvest stage of full fruit maturity showed better results for seed quality. The six-day fermentation period after seed extraction provided better results for seed vigor.